Assessment of online teaching as teaching learning method among the university students in the COVID pandemic - Kumar, Binay; Prasad, Seema; Prasad, Nidhi (International Journal of Research in Medical Sciences, 2023)
Background: The urgent need to educate during COVID times has led to stresses and needs for reimagining the education system, and now the system is evolving and has led to organising and designing in the current scenario to reap the benefits. Method: A total of 600 electronic students in Bihar, India participated in the study conducted to assess the barrier and facilitator of online learning. Participants in the study were post-secondary students graduating in electronics stream. Access to the online platform was through mobile and mobile data was used for connecting to online platform like google classroom. Majority of them (42%) preferred traditional teaching and complained of health issues, eye strain and loss of concentration. Results: The study showed most commonly used gadget for online teaching was mobile (98.8%) and google meet was the most common connecting platform (66.8%). The most common challenge faced was network issue (68.3%). Average screen time spent was 4.5 hours, that leads to eye strain and mental fatigueness as most common symptom reported. Conclusions: The reflection on how teaching learning process evolved during pandemic and incorporating ideas to deal with challenges help us build education system that is resilient and help us embrace an evolving teaching learning format now and in future.